Interaction of GCAP1 with retinal guanylyl cyclase and calcium: sensitivity to fatty acylation - Peshenko, Igor V.; Olshevskaya, Elena V.; Dizhoor, Alexander M. (Frontiers in Molecular Neuroscience, 2012)
Guanylyl cyclase activating proteins (GCAP)1 are calcium/magnesium binding proteins within neuronal calcium sensor proteins group (NCS) of the EF-hand proteins superfamily. GCAPs activate retinal guanylyl cyclase (RetGC) in vertebrate photoreceptors in response to light-dependent fall of the intracellular free Ca2+ concentrations. GCAPs consist of four EF-hand domains and contain N-terminal fatty acylated glycine, which in GCAP1 is required for the normal activation of RetGC. We analyzed the effects of a substitution prohibiting N-myristoylation (Gly2 → Ala) on the ability of the recombinant GCAP1 to co-localize with its target enzyme when heterologously expressed in HEK293 cells. We also compared Ca2+ binding and RetGC-activating properties of the purified non-acylated G2A mutant and C14:0 acylated GCAP1 in vitro. The G2A GCAP1 expressed with a C-terminal GFP tag was able to co-localize with the cyclase, albeit less efficiently than the wild type, but much less effectively stimulated cyclase activity in vitro. Ca2+ binding isotherm of the G2A GCAP1 was slightly shifted toward higher free Ca2+ concentrations and so was Ca2+ sensitivity of RetGC reconstituted with the non-acylated mutant. At the same time, myristoylation had little effect on the high-affinity Ca2+-binding in the EF-hand that is proximal to the myristoyl residue in the three-dimensional GCAP1 structure. These data indicate that the N-terminal fatty acyl group may alter the activity of EF-hands in the distal portion of the GCAP1 molecule via presently unknown intramolecular mechanism.